2004
DOI: 10.1111/j.1460-9568.2004.03240.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐dependent subthreshold oscillations determine bursting activity induced by N‐methyl‐d‐aspartate in rat subthalamic neurons in vitro

Abstract: We used whole-cell patch recordings in current clamp to investigate the ionic dependence of burst firing induced by N-methyl-d-aspartate (NMDA) in neurons of the subthalamic nucleus (STN) in slices of rat brain. NMDA (20 microm) converted single-spike firing to burst firing in 87% of STN neurons tested. NMDA-induced bursting was blocked by AP5 (50 microm), and was not mimicked by the non-NMDA receptor agonist AMPA (0.6 microm). Tetrodotoxin (1 microm) converted bursts to oscillations of membrane potential, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 71 publications
(78 reference statements)
1
51
0
Order By: Relevance
“…For example, CAN channels take part in plateau potential generation and persistent spiking in entorhinal cortex neurons (Egorov et al 2002), in DAPs in myenteric neurons (Vogalis et al 2002), and in after-depolarization and burst after discharge in rat neocortical neurons (Kang et al 1998;Aoyagi et al 2002). I CAN appears to have higher calcium sensitivity than other Ca 2+ -activated currents, such as I BK and I SK (Zhu et al 2004). The voltage-dependence of opening of CAN channels recently was reported in several excitable cells, including in rat and human cardiomyocytes (Guinamard et al 2002(Guinamard et al , 2004 and in hamster vomeronasal sensory neurons (Liman 2003).…”
Section: Ionic and Compartmental Mechanisms Of The Dapmentioning
confidence: 99%
“…For example, CAN channels take part in plateau potential generation and persistent spiking in entorhinal cortex neurons (Egorov et al 2002), in DAPs in myenteric neurons (Vogalis et al 2002), and in after-depolarization and burst after discharge in rat neocortical neurons (Kang et al 1998;Aoyagi et al 2002). I CAN appears to have higher calcium sensitivity than other Ca 2+ -activated currents, such as I BK and I SK (Zhu et al 2004). The voltage-dependence of opening of CAN channels recently was reported in several excitable cells, including in rat and human cardiomyocytes (Guinamard et al 2002(Guinamard et al , 2004 and in hamster vomeronasal sensory neurons (Liman 2003).…”
Section: Ionic and Compartmental Mechanisms Of The Dapmentioning
confidence: 99%
“…Cells that lack the plateau have been reported to similarly lack the capacity to exhibit burst firing (Beurrier et al, 1999). Flufenamic acid abolishes NMDA-induced bursting, suggesting that the presence of the plateau potential leads to the emergence of more bursty firing patterns in these neurons (Zhu et al, 2004). Thus, the plateau potential can control the discharge pattern of neurons by increasing their excitability and allowing them to fire in bursts.…”
Section: Plateau Potentials In Other Neuronsmentioning
confidence: 99%
“…I CAN and its associated plateau potential is important in controlling the firing pattern of subthalamic nucleus neurons which exhibit tonic, single spike firing, burst firing, as well as a quiescent plateau depolarization under some conditions (Beurrier et al, 1999;Zhu et al, 2004;Kass and Mintz, 2006). Burst firing can be observed in these neurons after release of hyperpolarizing current pulses or application of NMDA, both of which also elicit the plateau potential in subthalamic neurons (Beurrier et al, 1999;Zhu et al, 2004Zhu et al, , 2005. Cells that lack the plateau have been reported to similarly lack the capacity to exhibit burst firing (Beurrier et al, 1999).…”
Section: Plateau Potentials In Other Neuronsmentioning
confidence: 99%
“…To functionally test that idazoxan alters neurotransmitter release from presynaptic terminals, we inhibited synaptic transmission in brain slices by perfusion of TTX. It has been shown that plateau potentials do not rely on synaptic transmission (Beurrier et al, 1999;Baufreton et al, 2001;Zhu et al, 2004). Nevertheless, glutamate release presumably controls plateau potential potency, because agonists and antagonists of metabotropic glutamate receptors interfere with plateau potential and burst-firing activation (Awad et al, 2000;Zhu et al, 2004Zhu et al, , 2005.…”
Section: Idazoxan Has a Presynaptic Actionmentioning
confidence: 99%